Evaluation of phase angle measurements and nutrient consumption by bioelectrical impedance method of 20-65 years old women: Evaluation of Phase Angle Measurements and Nutrient Consumption by Bioelectrical Impedance Method. - Koseoglu, Sabiha Zeynep Aydenk; Dogrusoy, Meryem (Progress in Nutrition, 2020)
Background/Objectives: This study was carried out to determine the nutritional status of women between the ages of 20-65 and to evaluate the relationship between phase angles and nutrition by Bioelectric Impedance Analysis (BIA) method. 75 volunteer women between the ages of 20-65 who applied to a special cliniç were included to survey. Subjects (or Materials) and Methods: The application of questionnaire form that is aimed at general features nutrition behaviours, nutrient frequency of individuals and anthropometric measurements and nutrient consumption of individuals were recorded. The mean age was 39.4 ± 9.6 years and the mean body mass index was 28.7 ± 6.1 kg/m2. Results: It was determined that 17.3% of the participants did not skip meals, 82.7% of them skipped meals and the most skipped main meal was lunch with 53.3%. The ratio of daily energy taken from carbohydrate was lower than recommended (47 ± 8.7%), while the ratio of fat from fat was higher than recommended (37.8 ± 6.4%). Phase angle averages are 5.9 ± 0.80. Conclusions: There was no relationship between the parameters such as age groups, BMI groups, physical activity status and disease status of participants and phase angle values. A weak positive correlation was found between the body mass index and phase angle values of the participants (p=0.040, p<0.05). There was a moderately positive correlation between body muscle and phase angle values (p=0.000, p<0.05).According to the results of the study, It was seen that body mass indexes and body muscle amounts increased and phase angle values increased.